Development of Breast Phantom for Clinical Simulation and Educational Purposes (Journal of Science and Technology, 2024)
The development of a breast phantom for clinical and educational purposes is critical to providing a realistic and standardized model for training healthcare personnel in breast examination procedures, image interpretation, quality control, and procedure skills. Many current phantoms tend to fall short in providing realistic stiffness and acoustic attenuation. A gelatin-water mixture was used to make a tissue-like breast phantom. Gelatin was chosen for its biocompatibility, non- toxicity, and ability to replicate the mechanical and radiological properties of human soft tissue. Following the phantom’s fabrication, Computed Tomography (CT) imaging was used to calculate its Hounsfield units (HU), a measure of tissue density in comparison to water. The resulting HU value was then utilized to determine the phantom’s Relative Electron Density (RED), which is an important metric in determining if the phantom is suitable as a proxy for human tissue. The phantom’s computed RED value of 1.012 ± 0.036 is within the tolerance range of the typical RED of human breast tissue (0.976), with a 3.6% margin of error. This error percentage is due to the difficulties in correctly reproducing the varied makeup of human breast tissue, which includes a complex blend of glandular, fatty, and connective components. Despite this, the breast phantom has potential as a replacement for real human breast tissue, making it useful in research, clinical practice, education, and quality assurance. This study contributes to Sustainable Development Goal 3: Good Health and Well-being by developing technology and strategies for early detection and treatment of breast cancer. By improving the accuracy of breast imaging technology, this work adds to the larger goal of guaranteeing healthy lives and fostering well-being of people.